Multiple topologies from glycopolypeptide-dendron conjugate self-assembly: nanorods, micelles, and organogels - Pati, Debasis; Kalva, Nagendra; Das, Soumen; Kumaraswamy, Guruswamy; Sen Gupta, Sayam; Ambade, Ashootosh V. (Journal of the American Chemical Society, 2012)
Glycopolypeptides (GPs) were synthesized by ring-opening polymerization of glycosylated N-carboxyanhydride monomer and attached to hydrophobic dendrons at one chain end by ``click'' reaction to obtain amphiphilic anisotropic macromolecules. We show that by varying polypeptide chain length and dendron generation, an organogel was obtained in dimethylsulfoxide, while nanorods and micellar aggregates were observed in aqueous solutions. Assemblies in water were characterized by electron microscopy and dye encapsulation. Secondary structure of the GP chain was shown to affect the morphology, whereas the chain length of the poly(ethylene glycol) linker between the GP and dendron did not alter rod-like assemblies. Bioactive surface chemistry of these assemblies displaying carbohydrate groups was demonstrated by interaction of mannose-functionalized nanorods with ConA.